Pharmacogenetics of human ABC transporter ABCC11: new insights into apocrine gland growth and metabolite secretion - Ishikawa, Toshihisa; Toyoda, Yu; Yoshiura, Koh-ichiro; Niikawa, Norio (Frontiers in Genetics, 2013)
Cell secretion is an important physiological process that ensures smooth metabolic activities and tissue repair as well as growth and immunological functions in the body. Apocrine secretion occurs when the secretory process is accomplished with a partial loss of cell cytoplasm. The secretory materials are contained within secretory vesicles and are released during secretion as cytoplasmic fragments into the glandular lumen or interstitial space. The recent finding that the nonsynonymous SNP 538G>A (rs17822931; Gly180Arg) in the ABCC11 gene determines the type of earwax in humans has shed light on the novel function of this ABC transporter in apocrine glands. The wild type (Gly180) of ABCC11 is associated with wet-type earwax, axillary osmidrosis, and colostrum secretion from the mammary gland as well as the potential risk of mastopathy. Furthermore, the SNP (538G>A) in the ABCC11 gene is suggested to be a clinical biomarker for the prediction of chemotherapeutic efficacy. The aim of this review article is to provide an overview on the discovery and characterization of genetic polymorphisms in the human ABCC11 gene and to explain the impact of ABCC11 538G>A on the apocrine phenotype as well as the anthropological aspect of this SNP in the ABCC11 gene and patients’ response to nucleoside-based chemotherapy.